Exploring the Gender Gap in Science, Technology, Engineering, and Mathematics (STEM), and Soft Skills, and Knowledge of Role of Models Among Students in Rural Uganda (Journal of Education and Development, 2019)
Background: Globally, women’s representation in STEM fields remains significantly lower than that of men. Studies assessing the STEM gender gap in disadvantaged rural-based schools are lacking. Objective: To examine the gender differences in attitudes towards STEM and soft skills, and knowledge of role models among students of Nakivale secondary school in Nakivale refugee settlement, southwestern Uganda. Methods: We employed a cross sectional study design that administered pilot tested questionnaires to 111 secondary school students in Nakivale secondary school. Results: More girls than boys reported negative attitudes towards STEM. Both boys and girls demonstrated low attitudes towards the 21st century skills (such as goal setting, leadership skills, team work skills, time management and computer/internet skills), low intentions of pursuing STEM-related subjects in future, as well as limited exposure to STEM role models. Implication: Interventions to address girls’ negative attitudes towards STEM, improve students’ 21st century skills, develop students’ interest in STEM subjects/careers, and link students to role models are urgently needed especially in marginalized areas such as refugee settlements.